ABOUT THE PROBLEMS OF ENSURING THE ACCURACY OF THE RELATED POSITION OF PARTS SURFACES DURING PROCESSING - Khaydarov Ahmadali Kambarovich; Rakhmatov Abdukodir Qobuljon ogli (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the issues of ensuring the accuracy of the relative position of the surfaces of the part. It is noted that the existing regulatory documents do not allow to unambiguously and correctly set the dimensions and parameters of the relative position of the surfaces in the drawing. It is shown that the main problems arising in the process of technological preparation are associated with the ambiguity, incorrectness and inefficiency of specifying requirements for the relative position of surfaces on the drawings.